مستويات الحكم الرشيد في الادارات العامة دراسة استطلاعية لاراء عينة من ممثلي المجتمع في ادارة زاخو - نوري, د. ره نج محمد; طاهر, كوهدار شيخو; أحمد, شيماء علي; أحمد, هاشم علي (Sulaimani Journal for Humanities, 2023)
The research deals with one of the most important vital topics in the administrative sciences, and it revolves around diagnosing the certainty of the indicators of good governance in public administrations. The research includes a theoretical presentation of good governance concept based on the most agreed-upon theoretical propositions on its measurement indicators to include four indicators: (Justice & Law, Participation & consensus, Transparency, Accountability and Responsive). The research aims to identify the most important indicators of good governance measuring and the level of those indicators in the field. The research relied on a questionnaire to collect data from the field Based on the opinions of the research sample, which included representatives of civil society and included all the representatives of the residential shops, number of investors, members of parliament and lawyers within the administrative boundaries of the Zakho administration, which were recently established in the Kurdistan Region -Iraq.The sample was (122) based on the number of returned and valid forms for analysis, and the statistical tools were relied upon, including frequencies, percentages, arithmetic averages, and standard deviations, and the research reached a set of results that proved the validity of the hypothesis for the presence of indicators of good governance in the Zakho administration, and that there are high levels of indicators of justice, law and transparency as well as the existence of a variation in the levels of indicators. The research recommended the need to enhance participation and consensus, which achieved lower levels compared to other indicators in this research. aspects that were not covered by the research.
Keywords: Good Governance; indicators of good governance; administration of Zakho